Role of echocardiography in percutaneous occlusion of the left atrial appendage - Mráz, Tomáš; Neužil, Petr; Mandysová, Eva; Niederle, Petr; Reddy, Vivek Y (Echocardiography, 2007)
Percutaneous occlusion of the left atrial appendage (LAA) is a modern alternative for the treatment of patients with atrial fibrillation (AF) and with a high risk of stroke who are not eligible for long-term anticoagulation therapy. Echocardiography plays a significant role in selecting patients, guiding the procedure, and in the post-procedural follow-up. OBJECTIVES AND METHODS: To test the role of transesophageal echocardiography (TEE) and intracardiac echocardiography (ICE) in facilitating and shortening the procedure. RESULTS: ICE represents a more convenient approach in patients who are not under generally anesthesia and helps to facilitate transseptal puncture. On the other hand, TEE, having the ability to rotate the image plane, helps to better determine the position of the occluder. CONCLUSIONS: Echocardiographic guidance of this procedure is essential. Which approach will be preferred will depend on the development of these two methods.
Keywords: Echocardiography, Doppler, Color; balónková okluze; Female; fluoroskopie; Atrial Fibrillation; Atrial Appendage; Postoperative Period; peroperační doba; výsledek terapie; ženské pohlaví; lidé; Fluoroscopy; Treatment Outcome; Aged, 80 and over; následné studie; Middle Aged; pooperační období; Follow-Up Studies; Male; Aged; kontrastní látky; Echocardiography, Transesophageal; barevná dopplerovská echokardiografie; echokardiografie transezofageální; fibrilace síní; lidé středního věku; senioři nad 80 let; senioři; mužské pohlaví; síňové ouško; Contrast Media; Balloon Occlusion; Intraoperative Period; Humans